ANALYSIS OF FOOD SECURITY DISPARITIES IN CENTRAL JAVA: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - Lestari, Retna Dewi; Suhatmi, Erna Chotidjah; Hayati, Septy Dhian Nur; Pramudita, Willy (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
The purpose of this study is to examine the degree of GDP inequality between Central Java Province's districts and cities. This study's methodology is the Theil Index, which uses secondary data from GDP based on relevant prices for the business sector in 2024 that were obtained from the Central Statistics Agency (BPS). According to the study's findings, the degree of inequality in Central Java Province is indicated by the Theil Index, which has a value of 0.837, or nearly 1. This value shows that there is an uneven distribution of GDP between regions, with Semarang City having the highest GDP at 208,797 and Magelang City having the lowest at 7,690. Although there are still disparities or inequality between districts or cities due to variations in the GDP distribution process between Central Java regions, this indicates that the amount of disparity in the region is comparatively low. The processing industry sector is the largest contributor to Central Java's GDP, while other services are the least significant contributor.